SOSIALISASI PENDIDIKAN ASRAMA SEBAGAI PEMBENTUKAN KARAKTER SISWA PADA AL-IHSAN BOARDING SCHOOL (STUDI TENTANG LEMBAGA PENDIDIKAN SEBAGAI SOSIALISASI PEMBENTUK KEPRIBADIAN DI MA AL-IHSAN BOARDING SCHOOL KUBANG RAYA, KAMPAR â RIAU) - Wati, Setio; Yusuf, Yusmar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in the MA Al-Ihsan Boarding School Kubang Raya, Kampar - RIAU. IBS is Fullday School, learning load settings adjust the allocation of time specified in the curriculum structure. Education program is 54 hours of lessons each week. Every hour lesson duration 45 minutes, so there is a difference of 10 hours of national education standards. 10 hours of lessons are used for extracurricular mandatory 6 JP, 2 JP for extracurricular options, and 2 JP used for self-development (mentoring). The addition of more based on the analysis of global excellence of the school. In the case of the IBS aims to shape the character of their students become the generation that Islamic morals. The purpose of this study is: To determine the IBS method in shaping the personality of students. To determine changes in behavior or personality of students after school at IBS. To find out the student application to the environment or the surrounding community.The samples in this study is the quota sampling technique is a technique to determine the number of samples of the desired population as many as 53 respondents. The method I use in this research is descriptive analysis, which analyzes the data collected, tabulated according to the type of data and present the results of processing the data in tabular form and provide information by linking theory in accordance with the existing problems and menginterprtasikan against relevant results later be concluded.Based on this study, it can be stated that the success of IBS in shaping the personality of students still have not reached as expected. Known from the recapitulation of the 10 sub respondents saying "Yes" as many as 23 respondents or 43.40%. That is yet to reach 50% of students / i grade 2 MA were successfully formed his personality as expected IBS. While respondents expressed sometimes as many as 27 respondents or 50.94%.Keywords: Socialization, Boarding School, Education System